Prevalência de parasitos intestinais em crianças de idade pré-escolar em centros municipais de educação infantil em região de fronteira - Foz do Iguaçu - Carvalho, Fernanda Ferreira (2017)
Foz do Iguaçu has today more than 81 ethnicities, associated to a wide cultural diversity they contribute to the divergence of hygienic habits, resulting in precarious sanitary conditions. Fir this reason, the city government has been presenting several changes in public health area. The city is also located on a tri-border border area, about 7 km from Ciudad Del Este (Paraguay) and 10 km from Puerto Iguazu (Argentina). Its main economic product is Tourism, due to the relevance of the Iguazu Falls, considered one of the seven wonders of nature and Itaipu Hydroelectric Power Plant, which is on the border of Brazil and Paraguay. Because of the construction of the Hydroelectric Power Plant, in just 20 years, Foz do Iguaçu has grown by 383% in the total population of the city, generating a great job offer. Due to the increasing number of women entering the labor market, the Municipal Early Childhood Centers (CMEIs) have been a reality in the life of families, as this is the place where many children spend most of their time while mothers are at work. These institutions play an important role in the development of children as a whole, mainly referring to the intellectual, physical, social and psychological aspects. Children attending CMEIs are more susceptible to infections than those who are kept in their homes, which can be explained by the large interpersonal contact provided by the collective environments. To verify the prevalence of parasitic diseases among children attending CMEIs in Foz do Iguaçu and to analyze the possible relationship with the socioeconomic, environmental and hygienic scenario of children, parents and caregivers. This is a field research, with descriptive and quantitative approaches. The studied population consisted of all pre-school children aged from 3 to 5 years old, enrolled in CMEIs A and B, and parents and/or guardians working with sampling by convenience. The feces of the children were collected and then sent for analysis in the Environmental Laboratory of the Itaipu Hydroelectric Power Plant. In addition, a questionnaire was applied to the parents or guardians of the children, containing 19 closed questions, regarding the factors that contribute to the merge of parasitic diseases. Data were analyzed by the BioEstat 5.3® program and, the level of significance was considered at 5%. Results: A total of 82 fecal samples were analyzed from February to June 2016. Positive results for parasites were found in 38.8% of them. The following etiological agents were found: Giardia duodenalis (28,0%), Hymenolepis nana (3,6%), Ascaris lumbricoides (2,4%), Entamoeba coli (2,4%) and Enterobius vermicularis (2,4%). Regarding the degree of parasitism, 35.0% of the children presented monoparasitism and only 4% presented biparasitism, and there were no cases of polyparasitism. The parents and guardians of the parasitized children (32/82) received the antiparasitic medication prescription (metronidazole) and the medicament for the treatment of the children. In addition, they received guidance in order to prevent the emergence of new cases. The most affected gender by parasites was the male (20/41), followed by the female (12/41), (p<0.05) in the age range of 3 to 4 years (84.3%). The socioeconomic profile revealed that the level of schooling of mothers, complete secondary education (15/29 - p<0.05), and incomplete high school parents (13/24 - p>0.05), family income up to one Minimum wage (19/47 - p<0.05), residential structure with piped water and treated with chlorine (32/80 - p<0.05), waste disposal by means of cesspool (12/36 - p<0.05), may have influenced the average incidence of parasitism, as well as the aspects related to the habit of washing hands after diaper change (21/47 - p<0.05) and the health of the child, the taking of feces exams (19/45), abdominal pain (25/65), nausea (31/79), vomiting (31/78), weight loss (28/71) and presence of formed faeces (17/43) ) (P<0.05). However, the prevalence of parasitoses was related to the form of cleaning foods (fruits, and vegetables), only with water (23/60 - p<0.05), with children who do not have the habit of washing their hands with soap before meals and after using the toilet (6/15 - p>0.05). Conclusion: The results indicate an important prevalence of intestinal parasitoses in children who live on the border area, in the age range of 3 to 5 years old, mainly giardiasis. The presence of parasitic diseases in this population provides an epidemiological profile that can help in the construction of public health policies which are more appropriate to this social reality, in order to contribute to the improvement of health education of the population, especially the family members responsible for the children who are the most affected by the to intestinal parasites. Keywords: parasitic